2002
DOI: 10.1111/j.1944-9720.2002.tb01883.x
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap: Discourse in Text‐Based Foreign Language Classrooms

Abstract: Abstract:This study investigated text-centered talk in an "Introduction to Hispanic Literature" universitylevel classroom. The study was framed within sociocultural theory (Vygotsky, 1978;Wertsch, , 1991

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 78 publications
2
36
0
1
Order By: Relevance
“…The question of propelling university language majors to the Advanced level has been investigated as a function of the “language‐literature (dis)connection” (Donato & Brooks, , p. 184), and several studies (Darhower, ; Mantero, ; Polio & Zyzik, ; Thoms, ; Zyzik & Polio, ) have shed light on the most prevalent discourse features in upper‐level Spanish literature courses that are most frequently populated by majors and minors, including prospective language teachers. These studies revealed that students, including teacher candidates, were typically not provided with opportunities to address a range of topics and tasks in the target language in a sustained manner that was conducive to developing Advanced proficiency.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The question of propelling university language majors to the Advanced level has been investigated as a function of the “language‐literature (dis)connection” (Donato & Brooks, , p. 184), and several studies (Darhower, ; Mantero, ; Polio & Zyzik, ; Thoms, ; Zyzik & Polio, ) have shed light on the most prevalent discourse features in upper‐level Spanish literature courses that are most frequently populated by majors and minors, including prospective language teachers. These studies revealed that students, including teacher candidates, were typically not provided with opportunities to address a range of topics and tasks in the target language in a sustained manner that was conducive to developing Advanced proficiency.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Alternatively, it may be the foundation of entire foreign/second language programs (e.g., Byrnes, Maxim, & Norris, ). The CBI approach may also be used in specific classes or courses within language programs: both courses that focus on content not traditionally considered part of the foreign/second language curriculum, such as the Italian social and physical geography course described in Rodgers (); and courses with a focus on content that conventionally tend to be part of such curricula, such as literature and culture courses (e.g., Mantero, ; Polio & Zyzik, 2009). The latter are generally referred to as content, content‐oriented, or subject matter courses.…”
Section: Introductionmentioning
confidence: 99%
“…Such results lead us to wonder what happens in the literary/cultural studies courses typical of upper division curricula in most university foreign language departments that focus almost exclusively on content with, at best, incidental focus on form (Zyzik & Polio, 2008). These courses would appear to operate under the assumption that students already possess adequate language skills to be able to access and discuss the content, that instructors no longer need to give explicit attention to language development, and that students are making incidental progress in their language abilities, that is, that they are learning by default (Donato & Brooks, 2004; Mantero, ; Polio & Zyzik, 2009). However, according to Lyster (, ), although an incidental approach to language may be typical of communicative and content‐based classroom settings in general, it does not lead to sustained language development on the part of the learners.…”
mentioning
confidence: 99%
“…Since the above descriptive framework aims to describe universal features of ELT textbooks, it can be used to describe ELT textbooks in any teaching and learning context. In particular, when conducting description of classroom activities for in-use evaluation (i.e., category 6), researchers could use speech function analysis (Eggins & Slade, 1997;Harman & Zhang, 2015), focusing on what linguistics resources are taught for later evaluation, rather than just focusing on interactional patterns as identified in previous research (c.f., Mantero, 2002;Nahrkhalaji, 2012).…”
Section: Systemic Functional Linguistic-based Elt Textbook Analysismentioning
confidence: 99%
“…Through revealing interactions among teacher, student, and textbook Santos highlighted that the value of the textbook content is dynamically deconstructed, depending on the teacher's teaching style. Mantero (2002) also investigated a textbook-centered Spanish literature course in an American college with the purpose of revealing the triadic relationship between the teacher, textbook, and students' learning of Spanish as a foreign language. Based on nine full weeks of observation, Mantero, by means of conversational analysis (Drew & Heritage, 1992; see also Sacks, Schegloff, & Jefferson, 1974), analyzed and evaluated the textbook-centered classroom interactions and concluded that the instructor in this foreign language class initiated the most of the dialogues in the textbook-centered classroom and did not take full advantage of opportunities to help learners develop topic-based discourse, which was in the language textbook they were using.…”
Section: In-use Elt Textbook Evaluationmentioning
confidence: 99%